Understanding digital cinema : a professional handbook - Swartz, Charles S. (Focal Press, 2005)
UNDERSTANDING DIGITAL CINEMA: A PROFESSIONAL HANDBOOK is a comprehensive resource on all aspects of finishing, distributing and displaying film digitally. For technical professionals as well as non-technical decision-makers, the book is a detailed exploration of every component of the process, from mastering to theater management. * An overview of digital cinema system requirements * Post production work flow * Color in digital cinema * The digital cinema mastering process * Fundamentals of compression * Security * Basics of audio * Digital distribution * Digital projection technology * Theater systems * The international perspective: Views from Europe, Asia and Latin America * A realistic assessment of the future of digital cinema With contributions by: Richard Crudo, President, American Society of Cinematographers Leon Silverman, Executive Vice President, Laser Pacific Media Corporation Charles Poynton, Color Scientist Chris Carey, Senior Vice President, Studio New Technology, The Walt Disney Studios Bob Lambert, Corporate Senior Vice President New Technology & New Media, The Walt Disney Company Bill Kinder, Pixar Animation Studios Glenn Kennel, DLP Cinema Peter Symes, Manager, Advanced Technology, Thomson Broadcast & Media Solutions Robert Schumann, President, Cinea, Inc., A Subsidiary of Dolby Labs David Gray, Vice President, Production Services, Dolby Laboratories, Inc. Darcy Antonellis, Executive Vice President, Distribution and Technology Operations Warner Bros. Technical Operations Inc. and Senior Vice President, Worldwide Anti-Piracy Operations Warner Bros. Entertainment Inc. Matt Cowan, Principal and Founder, Entertainment Technology Consultants Loren Nielsen, Principal and Founder, Entertainment Technology Consultants Michael Karagosian, Partner, Karagosian MacCalla Partners (KMP) Peter Wilson, Vice President, Display Technologies, Snell and Wilcox Ltd. Patrick Von Sychowski, Senior Analyst, Screen Digest Wendy Aylsworth, Vice President of Technology, Warner Bros. Technical Operations Inc. * Learn how to manage the change and control costs, from a "who's who" list of the leaders in this ground-breaking field *Walk away from reading this book with an essential understanding of digital cinema today * Understand the benefits of the transition to digital cinema